Acid and alkali resistant anti-pollution nanofiltration membrane and preparation method thereof

Through ultraviolet light-induced graft polymerization technology, a new covalent bond structure is constructed on the surface of the nanofiltration membrane, which solves the problems of instability and pollution of traditional nanofiltration membranes in acid/alkali environments, and achieves efficient acid/alkali stability and resistance Pollution performance reduces production costs.

CN119186272APending Publication Date: 2024-12-27BEIJING NORMAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411354168.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional nanofiltration membranes are unstable in acid/alkali environments and are prone to contamination, which affects their separation performance. The resistance of existing acid- and alkali-resistant membrane materials is limited and cost is high.

Method used

UV light triggers graft polymerization on the surface of the porous membrane to construct a new covalent bond chemical structure. Vinyl hydrophilic monomers and zwitterionic monomers are used to form nanofiltration membranes that are anti-pollution and anti-biological pollution. .

Benefits of technology

It improves the stability and anti-pollution performance of the membrane in a strong acid/strong alkali environment, reduces production costs, and achieves efficient separation performance in acidic or alkaline wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186272A_ABST
    Figure CN119186272A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a novel acid and alkali resistant and anti-pollution nanofiltration membrane, and belongs to the technical field of membrane preparation. The preparation method comprises the following steps: firstly, generating active free radicals on the surface of a membrane through ultraviolet irradiation by utilizing a photoinitiator, and then grafting a hydrophilic monomer containing vinyl on an ultrafiltration bottom membrane under ultraviolet irradiation to form a compact active separation layer. As the active layer adopts a carbon-carbon covalent bond cross-linked network as a main chemical structure, stable ion separation efficiency can be maintained in strong acid (20% (w / v) sulfuric acid) and strong alkali (1mol / L sodium hydroxide) environments. Meanwhile, hydrophilic groups of poly-zwitterions or polyacrylic acid endow the membrane with excellent anti-pollution performance, and the membrane can be effectively prevented from biological pollution and protein pollution. The preparation method of the nanofiltration membrane with a brand new chemical structure, which is different from the traditional polyamide, greatly improves the acid-base stability of the nanofiltration membrane, and promotes the application of the nanofiltration membrane in strong acid, strong alkali and high-pollution environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane preparation, and in particular relates to an acid-base resistant and pollution-resistant nanofiltration membrane and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of petrochemical, hydrometallurgy, mining, textile production, leather industry and electronic industry, a large amount of acid / alkaline wastewater containing organic matter, inorganic salts and microorganisms and other pollutants has been continuously produced, posing a serious threat to the ecological environment and human health. Nanofiltration (NF) membrane separation technology has the advantages of high efficiency and low energy consumption. It can effectively remove organic molecules and multivalent ions in wastewater through size screening and Donan effect, and has attracted widespread attention in the fields of ion separation, water purification, and organic pollutant removal.

[0003] Traditional nanofiltration (NF) membranes usually use interfacial polymerization (IP) to form a polyamide (PA) active separation layer on the surface of a porous support layer to prepare a thin film composite NF membrane. However, in an acidic / alkaline environment, the amide bond is easily hydrolyzed, resulting in poor acid / alkaline stability of the traditional PA NF membrane, which greatly weakens the separation performance of the NF membrane. In existing research, the construction of strong acid and alkali resistant membranes mainly focuses on the preparation of non-polyamide chemical structures. Polysulfonamide, triazine ring and polyurea membrane materials have been designed to improve the acid resistance of NF membranes. However, these membranes are restricted by the permeability and selectivity "trade-off" effect, or the acid and alkali resistance is still limited. At the same time, membrane fouling is the main bottleneck affecting membrane separation performance. After the IP reaction of traditional NF membranes, negatively charged carboxyl groups and positively charged amino groups are usually retained in the PA layer. Natural organic matter and microorganisms in wastewater are easily attached to the membrane surface and inside through hydrophobic interaction, electrostatic interaction and ion bridging, making the membrane fouling more complicated.

[0004] In view of this, designing and preparing an excellent acid / alkali resistant and anti-fouling nanofiltration membrane is one of the problems that technicians in this field need to solve urgently. Graft polymerization on the surface of porous membrane initiated by ultraviolet light, based on the chemical stability and hydrophilicity of the grafted monomer, helps to develop a nanofiltration membrane with excellent acid / alkali stability and anti-fouling performance. Summary of the invention

[0005] The purpose of the present invention is to break through the limitation of weak acid and alkali stability of traditional polyamide chemical structure, and provide a new covalent bond chemical structure ion separation membrane material construction strategy, which can effectively resist the damage of strong acid / strong alkali environment to the membrane structure, and give the membrane good anti-biological and anti-organic pollution performance. The preparation process is simple, the cost is low, and the modified membrane can be reused, which can effectively solve the problems mentioned in the background technology.

[0006] The present invention provides an acid-base resistant and anti-pollution nanofiltration membrane and a preparation method thereof, which specifically comprises the following steps:

[0007] Step 1: Place the ultrafiltration membrane in a solution containing a photoinitiator under light-proof conditions, soak for a period of time, then take out the membrane, remove the residual solution on the membrane surface, make the membrane completely dry, and then seal and expose to light for a period of time;

[0008] Step 2: Immerse the membrane in step 1 in a vinyl-containing hydrophilic monomer solution for a period of time, and then expose it to light for a period of time to cause a monomer polymerization reaction.

[0009] Step 3: Take out the membrane prepared in step 2 and wash it several times with salt solution (only zwitterionic monomer is grafted) and ultrapure water in sequence to obtain a photo-initiated polymerization nanofiltration membrane.

[0010] In step 1 and step 2, the ultraviolet light grafting polymerization process needs to be carried out under the condition of avoiding natural light, and the light source is one of a UVLED lamp and a high-pressure mercury lamp, so that the irradiated ultraviolet wavelength is greater than 300nm.

[0011] In step one, the ultrafiltration bottom membrane includes one of polyethersulfone, polysulfone or polyvinylidene fluoride.

[0012] In step 1, the photoinitiator is one of benzophenone, thioxanthone and the like, the concentration of the photoinitiator is 0-10 mmol / L, and the membrane is immersed in the photoinitiator solution for 0-120 min.

[0013] In step 1, the film is exposed to ultraviolet light for 0-10 minutes.

[0014] In step 2, the hydrophilic monomer is a zwitterionic monomer, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide (DMAPS) or acrylic acid (AA).

[0015] In step 2, the concentration of the hydrophilic monomer solution is 5-100 mmol / L.

[0016] In step 2, the membrane is immersed in the hydrophilic monomer solution for 1-60 minutes.

[0017] In step 2, the film is exposed to ultraviolet light for 1-30 minutes.

[0018] In step three, the salt solution is a 1 mol / L sodium chloride aqueous solution.

[0019] In the process of preparing NF membrane by UV-initiated graft polymerization, the preparation conditions are optimized and the performance of NF membrane is regulated mainly by controlling factors such as the concentration of photoinitiator, UV irradiation time, and the type and concentration of hydrophilic monomers.

[0020] In the present invention, the acid and alkali resistance test of the modified nanofiltration membrane comprises the following steps:

[0021] The modified membrane was immersed in acid solution or alkaline solution of different concentrations for a period of time, during which the membrane was taken out at different time intervals, washed with pure water, and the membrane separation performance was measured.

[0022] Furthermore, the acid resistance test reagent is one of sulfuric acid, nitric acid, and hydrochloric acid solutions, with a concentration of 1-20wt%.

[0023] Furthermore, the alkali resistance test reagent is sodium hydroxide with a concentration of 0.1-5 mol / L.

[0024] Furthermore, the period of time is 0-60 days, and the interval time is 1-10 days.

[0025] Furthermore, the membrane separation performance is the membrane pure water permeation flux and the sodium sulfate or magnesium sulfate retention rate.

[0026] In the present invention, the anti-pollution performance test of the modified nanofiltration membrane includes an organic matter dynamic filtration experiment and an anti-biological adhesion and dynamic filtration experiment. The organic matter dynamic filtration experiment is at least one of bovine serum albumin, humic acid, sodium alginate, polysaccharide, and lysozyme, and the microorganism is at least one of Pseudomonas aeruginosa and Escherichia coli.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The photoinitiated polymerization nanofiltration membrane of the present invention has a simple manufacturing process, no toxic byproducts, and the raw materials are easily available and low in cost.

[0029] 2. The present invention breaks the traditional polyamide nanofiltration membrane structure and constructs a new carbon-carbon covalent bond-connected ion separation nanofiltration membrane, which greatly enhances the stability of the membrane in strong acid and strong alkali environments.

[0030] 3. The photoinitiated polymerization nanofiltration membrane of the present invention improves the anti-fouling performance of the separation layer due to the strong hydration brought by polyzwitterions or polyacrylic acid and the enhanced negative charge on the membrane surface, and can effectively prevent organic and biological contamination of the membrane.

[0031] 4. The photoinitiated polymerization nanofiltration membrane of the present invention can remove divalent salt ions and organic matter while avoiding membrane pollution and the influence of unstable acid and alkali resistance on membrane separation performance, and has good development prospects in the process of acidic or alkaline wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention and in conjunction with the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, wherein:

[0033] Figure 1 The scanning electron microscope images of the photopolymerized NF films obtained in Comparative Example 1 and Examples 1 and 2 are shown.

[0034] Figure 2 This is a test diagram of the long-term separation performance of the photopolymerized NF membrane acid resistance experiment in Example 4.

[0035] Figure 3 This is a test chart of the long-term separation performance of the photopolymerized NF membrane alkali resistance experiment in Example 5.

[0036] Figure 4 This is a graph showing the flux changes in the anti-protein pollution performance test of the photoinitiated polymerization NF membrane in Example 6.

[0037] Figure 5 This is a graph showing the flux changes in the dynamic filtration test of the photoinitiated polymerization NF membrane against biological contamination in Example 7.

[0038] Figure 6 This is a scanning electron microscope image of the photoinitiated polymerized NF film in the anti-biological contamination static adhesion test in Example 8. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be verified in conjunction with the specific embodiments of the present invention. The verified embodiments are only partial embodiments of the present invention. Based on the embodiments of the present invention, other embodiments obtained by researchers in the field without any creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] Example 1 provides an acid-base resistant and anti-pollution nanofiltration membrane and a preparation method thereof, and the specific steps are as follows:

[0042] (1) Dissolve 3 mmol / L benzophenone in 25 mL of ethanol solution. Place a polyethersulfone ultrafiltration membrane (MWCO: 50 kDa) in a culture dish containing the benzophenone solution for 60 min in a dark environment.

[0043] (2) taking out the membrane in step (1), removing the residual solution on the membrane surface, and completely drying the membrane surface, followed by UV irradiation for 1 min;

[0044] (3) Dissolve 10 mmol / L [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (DMAPS) in 25 mL of pure water, and immerse the membrane in step (2) in a culture dish containing the DMAPS aqueous solution for 10 min, followed by UV irradiation for 5 min;

[0045] (4) The photopolymerized NF membrane obtained in step (3) was taken out and washed several times with 1 mol / L sodium chloride solution and pure water in sequence (ie, a PES-g-PDMAPS membrane was obtained), and placed in pure water for later use.

[0046] Example 2

[0047] Example 2 provides an acid-base resistant and anti-pollution nanofiltration membrane and a preparation method thereof, and the specific steps are as follows:

[0048] (1) Dissolve 3 mmol / L benzophenone in 25 mL of ethanol solution. Place a polyethersulfone ultrafiltration membrane (MWCO: 50 kDa) in a culture dish containing the benzophenone solution for 60 min (with the front of the membrane facing up) under light-proof conditions.

[0049] (2) taking out the membrane in step (1), removing the residual solution on the membrane surface, and completely drying the membrane surface, followed by UV irradiation for 1 min;

[0050] (3) Dissolve 10 mmol / L acrylic acid (AA) in 25 mL of pure water, soak the membrane in step (2) in a culture dish containing the AA aqueous solution for 10 min, and then irradiate with UV light for 5 min;

[0051] (4) The photopolymerized NF membrane obtained in step (3) is taken out and washed several times with pure water (ie, a PES-g-PAA membrane is obtained) for later use.

[0052] from Figure 1 It can be seen that after the photo-initiated graft polymerization reaction, the membrane surface shows a more obvious protrusion structure than the PES base membrane, indicating that the functional monomer containing olefin groups can effectively construct an active layer on the surface of the ultrafiltration membrane through free radical polymerization.

[0053] Example 3

[0054] Example 3 provides a test and calculation of the basic separation performance of a nanofiltration membrane, and the specific steps are as follows:

[0055] The separation performance of the membrane was tested using a cross-flow filtration device. Before the test, the membranes prepared in Example 1 and Example 2 were pre-pressed with pure water until they were stable, and then the mass of the filtrate at each time point was recorded using an electronic balance connected to a computer (the test pressure was 0.5 MPa), and the water flux (J p, as shown in formula (1)). The membrane selectivity test stock solution uses a concentration of 1 g L -1 The salt solution is filtered and the salt concentration is tested by a conductivity meter before and after filtration. The salt retention rate (R) is calculated as shown in formula (2).

[0056]

[0057]

[0058] Among them, V(L), Δt(h) represent the volume and time of water penetration, A(m 2 ) is the effective filtration area of ​​the membrane. C p (mg L -1 ) is the salt filtrate concentration, C f (mg L -1 ) is the concentration of the salt stock solution.

[0059] The separation performances of the membranes prepared in Example 1 and Example 2 are shown in Table 1.

[0060] Table 1 Separation performance of PES-g-PDMAPS membrane in Example 1 and PES-g-PAA membrane in Example 2

[0061]

[0062] The results showed that the nanofiltration membrane was successfully prepared on the polyethersulfone ultrafiltration base membrane after photoinitiated graft polymerization.

[0063] Example 4

[0064] Example 4 provides a method for testing the acid resistance of a nanofiltration membrane, and the specific steps are as follows:

[0065] The membrane acid resistance experiment was conducted by long-term immersion. The membranes prepared in Example 1 and Example 2 were immersed in a 20% (w / v) sulfuric acid solution for 30 days at room temperature. During this period, the membranes were taken out at 0 days, 5 days, 10 days, 20 days and 30 days, and rinsed thoroughly with pure water. The pure water flux and sodium sulfate retention rate of the membranes were tested, and the changes in the initial flux and retention rate were observed.

[0066] like Figure 2 As shown, even after being immersed in the acid solution for 30 days, the PES-g-PDMAPS membrane prepared in Example 1 and the PES-g-PAA membrane prepared in Example 2 still maintain a relatively high ion rejection rate, indicating that the NF membrane has good acid resistance.

[0067] Example 5

[0068] Example 5 provides a method for testing the alkali resistance of a nanofiltration membrane, and the specific steps are as follows:

[0069] The membrane alkali resistance experiment adopts the method of long-term immersion. At room temperature, the membranes prepared in Example 1 and Example 2 were immersed in 2 mol / L sodium hydroxide solution for 20 days. During this period, the membranes were taken out at 0 days, 5 days, 10 days and 20 days respectively and rinsed thoroughly with pure water. The pure water flux and sodium sulfate retention rate of the membrane were tested, and the changes with the initial flux and retention rate were observed.

[0070] like Figure 3 As shown, even after being immersed in alkaline solution for 20 days, the PES-g-PDMAPS membrane prepared in Example 1 and the PES-g-PAA membrane prepared in Example 2 still maintained a relatively high ion rejection rate (the rejection rate for Na2SO4 remained at 89.3% and 90.3% of the initial value), indicating that the NF membrane has good acid resistance.

[0071] Example 6

[0072] Example 6 provides a nanofiltration membrane anti-protein pollution performance experiment, the specific steps are as follows:

[0073] Nanofiltration membrane anti-protein fouling performance test Bovine serum albumin (BSA) was used as a pollutant for dynamic filtration to evaluate the anti-protein fouling performance of the membranes prepared in Examples 1 and 2 and the commercial membrane NF90. First, the membrane was pre-pressed to reach a stable state. Thereafter, pure water was filtered for 60 min and 200 mg L -1 BSA solution, and the flux change was recorded. The membrane was then continuously rinsed for 30 min under low pressure and high speed water flow to remove reversible contaminants. Subsequently, the pure water and BSA filtration process was repeated again.

[0074] like Figure 4 As shown in the figure, during the test, the flux recovery rate of the PES-g-PDMAPS membrane prepared in Example 1 was 93%, the PES-g-PAA membrane prepared in Example 2 basically maintained a constant flux, and the flux of the NF90 membrane was significantly attenuated, and after cleaning, the flux was only restored to about 90% of the initial value. This shows that the photopolymerized NF membrane has excellent anti-pollution performance.

[0075] Example 7

[0076] Example 7 provides a nanofiltration membrane biofouling dynamic filtration experiment, the specific steps are as follows:

[0077] Nanofiltration membrane biofouling dynamic filtration experiment Pseudomonas aeruginosa (P. aeruginosa) was used as a model strain to evaluate the anti-biological fouling performance of the membranes prepared in Example 1 and Example 2 and the commercial membrane NF90. An appropriate amount of P. aeruginosa was inoculated into fresh LB liquid culture medium and cultured at 37°C and 180 rpm for about 10 hours until the OD of the bacterial solution reached 0.04. 600is 1.0 to obtain a concentration of 10 9 CFU mL -1 Take 10 mL of the solution and centrifuge it at 8000 rpm and 4°C for 15 min, then add the precipitate into 1 L of aqueous solution as the feed solution.

[0078] In the dynamic filtration of membrane biofouling, before the system is operated, it is pre-disinfected with 75% ethanol for 2 hours, and then rinsed with pure water for 2 hours. Then the membrane is installed in the membrane pool, and the membrane is pre-pressed at a pressure of 6 bar for 2 hours until the flux is stable. The flux at this time is recorded as J p0 , and then the bacterial liquid was filtered continuously for 24 hours, and the flux change was continuously observed, and the flux was recorded as J p .

[0079] from Figure 5 It can be seen that the flux of the NF90 membrane dropped sharply in the 24h dynamic filtration experiment, and the attenuation rate was close to 50%. The flux of the PES-g-PDMAPS membrane prepared in Example 1 was attenuated by about 18% in the 24h filtration experiment, and the flux attenuation rate of the PES-g-PAA membrane prepared in Example 2 was only 9%. This shows that the photoinitiated polymerization NF membranes in Examples 1 and 2 of the present invention have good anti-biological fouling performance.

[0080] Example 8

[0081] Example 8 provides a nanofiltration membrane anti-biological static adhesion test, the specific steps are as follows:

[0082] The nanofiltration membrane anti-biological static adhesion experiment was carried out with Pseudomonas aeruginosa (P. aeruginosa) as the model strain for short-term adhesion experiments. An appropriate amount of P. aeruginosa was inoculated into fresh LB liquid culture medium and cultured at 37°C and 180 rpm for about 10 hours until the OD of the bacterial solution reached 0. 600 is 1.0 to obtain a concentration of 10 9 CFU mL -1 The NF membranes and polyethersulfone (PES) ultrafiltration bottom membranes prepared in Example 1 and Example 2 were sterilized and cut into 2 x 2 cm 2 size and immersed in 5mL of 10 7 CFU mL -1LB bacterial suspension in a six-well plate. After culturing for 4 h at 37 ° C and 80 rpm, the membrane was removed and rinsed with sterilized PBS buffer (pH 7.2-7.4). The colony distribution of the NF membrane and PES ultrafiltration bottom membrane prepared in Example 1 and Example 2 was observed. The results are shown in Figure 6. Compared with the PES bottom membrane, there are fewer cells distributed on the surface of the PES-g-PDMAPS in Example 1 and the PES-g-PAA in Example 2. This is mainly due to the strongly hydrating zwitterionic groups in PDMAPS and the hydrophilic carboxyl groups in PAA.

[0083] Comparative Example 1

[0084] In Example 1 and Example 2, in order to compare and illustrate the morphological changes on the membrane surface after light-induced graft polymerization, a polyethersulfone (PES) ultrafiltration bottom membrane was set as a control group.

[0085] Comparative Example 2

[0086] In Example 1, for the convenience of comparison, a control group experiment without benzophenone (BP) initiation was set up, including the following steps:

[0087] (1) Weigh 10 mmol / L [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (DMAPS) and dissolve it in 25 mL of pure water. Soak a polyethersulfone ultrafiltration membrane (MWCO: 50 kDa) in a culture dish containing the DMAPS aqueous solution for 10 min, and then irradiate with UV light for 5 min.

[0088] (2) The photopolymerized NF film obtained in step (1) is taken out and washed several times with 1 mol / L sodium chloride solution and pure water in sequence for later use.

[0089] Comparative Example 3

[0090] In Example 2, for the convenience of comparison, a control group experiment without benzophenone (BP) initiation was set up, including the following steps:

[0091] (1) Weigh 10 mmol / L acrylic acid (AA) and dissolve it in 25 mL of pure water. Soak a polyethersulfone ultrafiltration membrane (MWCO: 50 kDa) in a culture dish containing the AA aqueous solution for 10 min, and then irradiate with UV light for 5 min.

[0092] (2) The photopolymerized NF film obtained in step (1) is taken out and washed with pure water several times for later use.

[0093] The separation performances of the membranes prepared in Comparative Examples 2 and 3 are shown in Table 2.

[0094] Table 2 Separation performance of membranes prepared in Comparative Example 2 and Comparative Example 3

[0095]

[0096] The results of the membranes prepared in Example 1 and Example 2 show that the presence of BP can lead to more PDMAPS or PAA being grafted onto the surface of the PES membrane, thereby forming a denser carbon-carbon bond network structure.

[0097] Comparative Example 4

[0098] In Example 4 and Example 5, in order to illustrate the excellent strong acid and alkali resistance of the photoinitiated polymerization NF membrane, a control experiment (traditional polyamide NF membrane) was set up. The preparation steps of the traditional polyamide NF membrane are as follows: First, a 0.3wt% PIP aqueous solution is spread on the surface of the PES ultrafiltration bottom membrane for 2 minutes to remove excess moisture on the membrane surface. Then the membrane is immersed in a n-hexane solution containing 0.2wt% TMC for interfacial polymerization reaction for 1 minute to form a polyamide active layer. The membrane is then taken out and washed with n-hexane, and dried at 60°C for 20 minutes to obtain a polyamide NF membrane.

[0099] The membrane water flux and salt rejection results are shown in Table 3.

[0100] Table 3 Comparative Example 4 membrane separation performance test results after immersion in acid / alkaline solution

[0101]

[0102] As can be seen from Table 1, compared with the NF membranes prepared in Examples 1 and 2, the conventional polyamide NF membrane in Comparative Example 4 experienced a significant increase in flux and a significant decrease in ion rejection in a very short time.

[0103] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the above-described embodiments are only a preferred implementation scheme of the present invention, which is only for illustrating the technical concept and features of the present invention, and cannot be used to limit the protection scope of the present invention. All equivalent technologies that are equivalently replaced or modified according to the concept of the present invention are protected by this patent.

Claims

1. An acid- and alkali-resistant and anti-pollution nanofiltration membrane and a preparation method thereof, characterized in that: The steps include: Step 1: Place the ultrafiltration membrane in a solution containing a photoinitiator under light-proof conditions, soak for a period of time, then take out the membrane, remove the residual solution on the membrane surface, make the membrane completely dry, and then seal and expose to light for a period of time; Step 2: Immerse the membrane in step 1 in a vinyl-containing hydrophilic monomer solution for a period of time, and then expose it to light for a period of time to cause a monomer polymerization reaction. Step 3: Take out the membrane prepared in step 2 and wash it several times with salt solution (only zwitterionic monomer is grafted) and ultrapure water in sequence to obtain a photo-initiated polymerization nanofiltration membrane.

2. The preparation method according to claim 1, characterized in that: In step 1 and step 2, the light source is a UVLED lamp or a high-pressure mercury lamp, and the light intensity is adjusted by adjusting the power and the distance and position between the film and the light source.

3. The preparation method according to claim 1, characterized in that: In step 1, the ultrafiltration bottom membrane is one of polyethersulfone (PES), polysulfone (PSF), and polyvinylidene fluoride (PVDF), but is not limited thereto.

4. The preparation method according to claim 1, characterized in that: In step 1, the types of photoinitiators include, but are not limited to, hydrogen abstraction type photoinitiators such as benzophenone, and the like. The solvents of the photoinitiators include, but are not limited to, ethanol, methanol, and the like.

5. The preparation method according to claim 1, characterized in that: In step 1, the concentration of the photoinitiator is 0-10 mmol / L, the membrane immersion time is 0-120 min, and the UV irradiation time is 0-10 min.

6. The preparation method according to claim 1, characterized in that: In step 2, the hydrophilic monomer containing vinyl group is sulfobetaine, carboxybetaine, phosphobetaine, etc. but not limited thereto, and the concentration of the hydrophilic monomer is 5-100 mmol / L.

7. The preparation method according to claim 1, characterized in that: In step 2, the membrane is immersed for 1-60 minutes and the UV irradiation time is 1-30 minutes.

8. The preparation method according to claim 1, characterized in that: In step three, the salt solution is an aqueous solution of sodium chloride, magnesium chloride, etc., with a concentration of 1 mol / L.

9. According to the acid-base resistant and anti-pollution nanofiltration membrane and the preparation method thereof as described in claims 1 to 8, the prepared nanofiltration membrane can maintain good extreme pH stability while achieving efficient divalent salt ion interception.

10. According to the acid-base resistant and anti-pollution nanofiltration membrane and the preparation method thereof as described in claims 1 to 8, the prepared nanofiltration membrane has good anti-pollution properties to natural organic matter and microorganisms, and can effectively prevent membrane pollution.

Citation Information

Cited By

  • Preparation method of high-flux anti-pollution nanofiltration membrane based on nanorods

    CN121198065A